2021
DOI: 10.1097/md.0000000000025983
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the severity of hypertriglyceridemia induced acute pancreatitis

Abstract: Hypertriglyceridemia induced acute pancreatitis (HTGP) was associated with increased risk of local complications, recurrent acute pancreatitis (AP), the frequency of other complications, and its high mortality as compared to other causes. Determining the factors associated with the severity of HTGP was necessary and important in the management of patients with AP.This study aims to examine the clinical and biochemical characteristics of HTGP patients, and to determine the factors associated with the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It is estimated that up to 85% of patients with severe HTG of any etiology will develop AP at some point in their life [ 30 ]. According to Retterstøl, K., et al, the prevalence of a history of AP is 17% in patients with severe HTG [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that up to 85% of patients with severe HTG of any etiology will develop AP at some point in their life [ 30 ]. According to Retterstøl, K., et al, the prevalence of a history of AP is 17% in patients with severe HTG [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thong et al found in a study that in a population with very severe HTG, 13.4% of patients with HTG-induced acute pancreatitis had dyslipidemia, 15.9% presented hypertension and 28% had type 2 diabetes mellitus [ 30 ]. In the present study, 49.28, 32.43, and 19.6% of patients were identified with dyslipidemia, hypertension, and DM2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is conflicting regarding the severity of HTG-AP when compared to other etiologies. However, many studies point out that HTG-AP causes the most severe form of AP with an increased risk of complications and mortality [ 2 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is a serious inflammatory condition of the pancreas associated with severe morbidity and mortality [ 1 ]. It is a highly prevalent gastrointestinal condition and one of the leading causes of hospitalization, with an incidence of 4/10,000 in western countries and rising [ 2 , 3 ]. Excessive alcohol use and gallstones are the most frequent etiologies for AP, constituting 80–90% of the cases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs included continuous variables: Respiratory rate (RR), heart rate (HR), systolic blood pressure, and diastolic blood pressure. Laboratory findings performed within 24 h of admission included WBC, NLR[ 14 ], RDW[ 19 ], platelet counts (PLT), mean platelet volume (MPV)[ 20 ], platelet distribution width (PDW)[ 21 ], total cholesterol (TC)[ 22 ], TG[ 6 ], high-density lipoprotein cholesterol level to low-density lipoprotein cholesterol level ratio (H/L ratio)[ 23 ], apolipoprotein A1 (ApoA1)[ 24 ], total bilirubin (TBIL), aspartate transaminase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), albumin (ALB)[ 25 ], blood urea nitrogen (BUN)[ 24 ], serum creatinine (Cr)[ 26 ], free triiodothyronine (fT3)[ 27 ], CRP, procalcitonin (PCT), serum sodium (Na), serum potassium (K), serum Ca 2+ , prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), fibrinogen (FIB)[ 28 ], and D-dimer levels[ 29 ]. Imaging results included the presence of a pleural effusion according to the chest X-ray within 24 h of admission[ 30 ].…”
Section: Methodsmentioning
confidence: 99%